Equilibrium solubility of carbon dioxide in 2(methylamino)ethanol - Haider, H.A.M.; Yusoff, Rozita; Aroua, M.K. (Fluid Phase Equilibria, 2011)
In this paper the equilibrium solubility of carbon dioxide in 1.0 M. 2.0 M and 4.0 M 2(methylamino)ethanol (MAE) is measured at 303, 313 and 333 K. and at CO(2) partial pressures ranging from 1 to 100 kPa using stirred cell reactor. The Kent-Eisenberg model was used to predict the solubility of carbon dioxide in MAE solutions. The equilibrium constant representing hydrolysis of carbamate ion is correlated with temperature, CO(2) partial pressure and amine concentration by non-linear regression, using experimental results of carbamate ion concentrations. The model predicted results showed good agreement with the experimental solubility results. The solubility profile of CO(2) in MAE showed better performance when compared with other commercial amines.